PubMed alternatives to search MEDLINE: An environmental scan - Arun Keepanasseril (Wolters Kluwer Medknow Publications, 2014)
The prime objective of this article is to introduce the newer methods to access, search and process MEDLINE citations. It also aims to provide a brief overview of each service's salient features. A targeted search was conducted in MEDLINE through the OVID gateway. This was followed with a search in Google Scholar as well as Google and Bing. Ninety-two web-based services that can be used to search MEDLINE were identified. The list was shortened to 24 by applying a set of relevancy criteria to select those services more relevant to general medical and dental users. Salient features of the selected services are outlined and a use case based classification of the system has been proposed to help dental practitioners and researchers select the appropriate service for a given purpose.